Uji sensitivitas dan spesifisitas perangkat lunak “Prediktor Karies Anak” (The sensitivity and specificity test of software for dental caries prediction in children) - Quroti A’yun; Julita Hendrartini; Al. Supartinah Santoso; Lukito Edi Lugroho (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: The prevalence of dental caries in children is high, therefore preventive actions is needed. So far the computer preventive actions is needed. So far the computer software that have been used for caries predictor is cariogram, which determine the condition of teeth and oral mouth. Recently which determine the condition of teeth and oral mouth. Recently and oral mouth. Recently mouth. Recently“Prediktor Karies Anak” (pediatric caries predictor) software have been developed not only determine the condition of teeth and software have been developed not only determine the condition of teeth and been developed not only determine the condition of teeth and oral mouth but also child’s behavior, maternal behavior, and the environment. behavior, maternal behavior, and the environment. Purpose: The objective of this study was to examine objective of this study was to examinethe sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of